Lecturers’ Perception on the Teacher Certification Program (PPG) for In-Service English Teachers at UNP in 2021 - Nisa, Tika Khairun; Tiarina, Yuli (Journal of English Language Teaching, 2024)
PPG (Teacher Professional Education) is a program aimed at preparing and producing qualified teachers. This program is designed to prepare teachers to become qualified teachers. This study investigates how lecturers perceive a teaching certification program for in-service English teachers focused on the implementation of deepening material through online self-study, lesson planning, and teaching practicum. This study's participants were eight lecturers who taught PPG Daljab in 2021 at Universitas Negeri Padang. The type of research used in this study is qualitative research. Data were gathered using open and closed questionnaires distributed via Google-form. This study's findings on deepening material through online self-study received positive feedback, with challenges and recommendations highlighted. Positive agreement is evident in the development of lesson plans, with some areas requiring attention and improvement. Although the teaching practicum received positive feedback, there are some issues that must be addressed. Overall, the study provides insight into teacher certification programs' in-service effectiveness, challenges, and enhancement suggestions.